Identification, Weighting, and Prioritization of Components and Indicators Determining the Circular Economy with a Marketing Approach - Mousavizadeh, Seyed Mojtaba; Nayebzadeh, Shahnaz; Hataminasab, Seyed Hassan; Tabatabaie Nasab, Zohreh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The goal of this study is to identify the components and indicators determining the circular economy with a marketing approach. Methodology: This study utilized a multi-criteria decision analysis (MCDA) approach, employing pairwise comparisons to assess the relative importance of different criteria and sub-criteria. The MCDA process was conducted using expert judgments gathered through structured questionnaires. The experts included professionals and academics from various fields related to business management, sustainability, and marketing. The weights and rankings of the criteria were determined using the Analytic Hierarchy Process (AHP) method, with consistency ratios calculated to ensure the reliability of the results. The findings were then analyzed and discussed in light of existing literature. Findings: The results revealed that among the criteria, entrepreneurial marketing (weight = 0.486) and product innovations (weight = 0.193) were identified as the most influential in enhancing organizational performance. Within entrepreneurial marketing, the sub-criterion increased competition, creativity, and innovation (weight = 0.601) was ranked highest. Sustainable development and cultural and attitudinal changes were also found to play significant roles, with energy sustainability (weight = 0.727) and cultural patterns and social welfare improvement (weight = 0.602) being the top-ranked sub-criteria. Environmental changes, though important, ranked lower in comparison. Conclusion: This study highlights the central role of entrepreneurial marketing and product innovations in organizational success, followed by sustainability efforts and cultural changes. The findings suggest that businesses should prioritize innovation, competition, and sustainability to remain competitive in a rapidly changing global market.